PROKR2 Mutations in Patients with Short Stature Who Have Isolated Growth Hormone Deficiency and Multiple Pituitary Hormone Deficiency - Aslı Derya Kardelen; Adam Najaflı; Firdevs Baş; Birsen Karaman; Güven Toksoy; Şükran Poyrazoğlu; Şahin Avcı; Umut Altunoğlu; Zehra Yavaş Abalı; Ayşe Pınar Öztürk; Esin Karakılıç Özturan; Seher Başaran; et al. (Galenos Yayincilik, 2023)
INTRODUCTION: Recent reports have indicated the role of the prokineticin receptor 2 gene (PROKR2) in the etiology of pituitary hormone deficiencies, suggesting a potential role for the PROK2 pathway in pituitary development, in addition to its role in gonadotropin releasing hormone-expressing neuron development. Here, we present the clinical and molecular findings of four patients with PROKR2 mutations. METHODS: Next-generation targeted sequencing was used to screen 25 genes in 59 unrelated patients with multiple pituitary hormone deficiency (MPHD), isolated growth hormone (GH) deficiency, or idiopathic short stature. RESULTS: Two different, very rare PROKR2 missense alterations classified as pathogenic (NM_144773.4: c.518T>G; NP_658986.1: p. (Leu173Arg)) and likely pathogenic (NM_144773.4: c.254G>A; NP_658986.1: p.(Arg85His)) were identified in four patients in heterozygous form. Patient 1 and Patient 2 presented with short stature and were diagnosed as GH deficiency. Patient 3 and Patient 4 presented with central hypothyroidism and cryptorchidism and were diagnosed as MPHD. No other pathogenic alterations were detected in the remaining 24 genes related to short stature, MPHD, and hypogonadotropic hypogonadism. Segregation analysis revealed asymptomatic or mildly affected carriers in the families. DISCUSSION AND CONCLUSION: PROKR2 dominance should be kept in mind as a very rare cause of GH deficiency and MPHD. Expressional variation or lack of penetrance may imply oligogenic inheritance or other environmental modifiers in individuals who are heterozygous carriers.